Influence of thermal memory on the thermoelastic bending component of photoacoustic response - Nešić Mioljub V. (Hemijska Industrija, 2011)
In this work, thermoelastic component of the photoacoustic response is derived, including thermal memory of the material. The comparison between this model and the classic one, which does not account for the influence of thermal memory is made. It has been noticed that the two models tend to overlap at very high and very low frequencies of the light modulation spectrum, while in the middle range some deviations become more apparent, which proves that thermal memory must be taken into account. It has also been shown that the limits of this range are the function of heat propagation velocity and thickness of the sample. Based upon the processing of obtained data, it has been concluded that the characteristics of the output signal, in the range of the interest, are highly influenced by thermal dynamic qualities, like heat diffusivity and thermal relaxation time, as well as the sample thickness.